Digitalization of Parliament: Implementation of E-Parliament in the Central Java Provincial DPRD - Dafana Khairunnisa; Fitriyah Fitriyah (Politeknik Siber Cerdika Internasional, 2026)
Background: An increasing trend in digital governance reforms is the influence on democratic processes, including in legislative institutions. Like e-parliament initiatives, that have changed the local legislatures (DPRD) in Indonesia to be more participatory, and more responsive to society. Yet their impact as platforms on substantive representation has not been sufficiently studied. Objective: This research aimed to examine the installation of E-Parliament in Central Java Provincial DPRD to broaden publication participation in it, in addition, as a medium for community representation. Methods: A qualitative case study/data were collected through semi-structured interviews with DPRD members, administrative stakeholders, and the public, as well as surveys and document review. A multi-actor methodology was utilised to obtain views from political actors, administrative actors, and citizens through digital platforms. Results: These results demonstrate that digital platforms add procedural transparency and responsiveness by strengthening the record-keeping and tracking of public hopes and desires. But since cultures tend to prefer local channels where direct interaction is frequent, it reinforces the role of relational legitimacy, although on informal grounds, leading to widespread use of informal channels. Digital inclusion is also shaped by how literacy and access differ. Conclusion: The article argues that while E-Parliament does improve procedural responsiveness, it does not ensure substantive responsiveness. Increasing digital literacy, ameliorating outreach capacities, and interfacing digital platforms with culturally embedded participatory practices are imperative for realizing equitable democratic engagement.